PEARSON'S CORRELATION ANALYSIS IN PREDICTING PSYCHOLOGICAL DISORDER CONDITIONS IN ONLINE GAME PLAYERS IN INDONESIA: A CASE STUDY ON VALORANT - Edwin Charley; Syaeful Anas Aklani (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2023)
In modern times, technology is developing very rapidly, especially in the gaming industry. This results in game addiction. Online game addiction is known as Internet Game Disorder (IGD). This can have an impact on other psychological disorders such as Attention Deficit Hyperactivity Disorder (ADHD), and Generalized Anxiety Disorder (GAD). This study aims to determine the relationship between Valorant game player statistics and IGD, ADHD, and GAD. The method used is a qualitative and quantitative approach. In the qualitative method, 30 samples of Indonesian valorant players were taken in filling out the questionnaire and in the quantitative method, 400 samples of Indonesian valorant players were taken using the Slovin formula to conduct interviews. The data obtained is applied simultaneously and looks for relationships between these data. Based on the results of qualitative and quantitative data analysis, the correlation results obtained for IGD, ADHD, and IGD have a very low relationship to player performance so player performance has a very low impact on the occurrence of psychological disorders.Keywords: Pearson Correlation, IGD, ADHD, GAD, Video Games.Di zaman modern, teknologi berkembang sangat pesat terutama pada industri game. Hal ini mengakibatkan terjadinya kecanduan game. Kecanduan game online dikenal sebagai Internet Game Disorder (IGD). Hal ini bisa berdampak pada gangguan psikologi lainnya seperti Attention Deficit Hyperactivity Disorder (ADHD), dan Generalized Anxiety Disorder (GAD). Penelitian ini bertujuan untuk mengetahui hubungan antara statistik pemain game Valorant dengan IGD, ADHD, dan GAD. Metode yang digunakan yaitu pendekatan kualitatif dan kuantitatif. Pada metode kualitatif, diambil sebanyak 30 sampel pemain valorant Indonesia dalam pengisian kuisioner dan pada metode kuantitatif, diambil sebanyak 400 sampel pemain valorant indonesia dengan perhitungan menggunakan rumus Slovin untuk melakukan wawancara. Data yang didapatkan diterapkan secara bersamaan dan mencari hubungan antara data - data tersebut. Berdasarkan hasil analisis data kualitatif dan kuantitatif, memperoleh hasil korelasi IGD, ADHD, dan IGD memiliki hubungan yang sangat rendah terhadap performa pemain sehingga performa pemain memiliki dampak yang sangat rendah terhadap terjadinya gangguan psikologis.Kata kunci: Korelasi Pearson, Psychological Disorder, SPSS, IGD, ADHD, GAD, Video games.